Keefektifan program konseling singkat berfokus solusi dalam LMS Schoology untuk meningkatkan perilaku hidup sehat siswa di masa pandemi Covid-19 - Kadek Suranata; Ifdil Ifdil (Jurnal Konseling dan Pendidikan, 2021)
The global Covid-19 pandemic has affected changes in various dimensions of life. In Indonesia, schools have adopted a policy of replacing face-to-face learning in schools with distance learning activities. The effect that occurs with learning activities at home is a decrease in healthy living behavior among students. This study aims to examine the effect of solution-focused brief counseling implemented through LMS Schoology to improve students’ healthy living behavior. This experimental study used a one-group pretest-posttest design. Of the 60 students who took part in the initial screening with the criteria for experiencing a healthy lifestyle disorder, only 15 students met the criteria. The Indonesian version of the Inventory Health-Promoting Lifestyle Profile [HPLP II] was used to measure students’ health behavior before and after participating in the intervention. The scale of acceptability, accessibility, feasibility (AAF) measured student responses to the acceptability and usefulness of the program. Analysis of research data related to the effect of an intervention on students’ healthy living behavior using a one-sample t-test. Student response data on the acceptability and usefulness of the program through descriptive analysis. The results showed that after participating in the program for an average of 8 weeks (an average of 16 LMS accesses), participants achieved a significant improvement in their average lifestyle and health (HPLP). The effect size of Cohen’s high d value shows a large effect size for this counseling program. AAF data also supports this result, with an average of 95% of students understanding the program and being able to implement it well, is accessible, and provides benefits for them. This research has theoretical and practical implications for guidance and counseling services in schools related to various dynamics that occur, including the condition of the Covid-19 Pandemic. Abstrak. Pandemi Covid-19 yang terjadi secara global memberikan dampak terhadap perubahan berbagai dimensi kehidupan. Di Indonesia, sekolah mengambil kebijakan dengan mengganti pembelajaran tatap muka di sekolah dengan kegiatan pembelajaran jarak jauh. Salah satu dampak yang terjadi dengan aktivitas pembelajaran di rumah adalah penurunan perilaku hidup sehat di kalangan siswa. Penelitian ini bertujuan untuk menguji pengaruh konseling singkat berfokus solusi yang dilaksanakan melalui LMS Schoology untuk meningkatkan perilaku hidup sehat siswa. Penelitian eksperimen ini menggunakan rancangan one group pretest-posttest. Dari 60 siswa yang mengikuti screening awal dengan kriteria dialaminya gangguan perilaku hidup sehat, hanya 15 siswa yang memenuhi kriteria. Inventory Health- Promoting Lifestyle Profile [HPLP II] versi Bahasa Indonesia digunakan untuk mengukur perilaku hidup sehat siswa sebelum dan setelah mengikuti intervensi. Respon siswa terhadap keberterimaan dan kebermanfaatan program diukur dengan skala acceptability, accessibility, feasibility (AAF). Analisis data penelitian terkait pengaruh intervensi terhadap perilaku hidup sehat siswa menggunakan one sample t-test. Data respon siswa terhadap keberterimaan dan kebermanfaatan program melalui analisis deskriptif. Hasil penelitian menunjukkan setelah mengikuti program selama rata-rata 8 minggu (rata-rata 16 kali akses LMS), partisipan mencapai peningkatan rata-rata gaya hidup dan kesehatan (HPLP) yang signifikan. Effect size dari nilai d oleh Cohen yang tinggi menunjukkan ukuran pengaruh yang besar dari program konseling ini. Data AAF juga mendukung hasil ini yaitu rata-rata 95% partisipan menyatakan bahwa program dapat dipahami dan dilaksanakan dengan baik, mudah diakses, serta memberikan bermanfaat bagi mereka. Penelitian ini berimplikasi secara teoritis dan praktis terhadap inovasi pelayanan bimbingan dan konseling di sekolah terkait dengan berbagai dinamika yang terjadi, termasuk kondisi Pandemic Covid-19